Ground support modelling involving large ground deformation : Simulation of field observations – Part 1 - Saiang, David; Nordlund, Erling (Luleå tekniska universitet, Geoteknologi, 2016)
The Kristineberg mine has a long history of large ground deformation which consequently incites ground control problems for the mine. Over the years the mine has developed various mining techniques, backfilling and ground support procedures to manage this problem. In general the ground control problems at the mine are highly influenced by the wall rock geology. The wall rock, that is the footwall and hanging wall, comprise of highly altered chlorite schist, which are internally referred to as talc-schist. They very often occur as seams with thickness barely ranging from 0.1 m to as wide as 3.0 m. Coupled with high ground stresses the talc squeezes and slides into the stope if undercut by the excavation, or either bends or bulges inwards when exposed but not undercut depending on the loading direction. The deformation magnitudes have often been reported to be in the order of 0.2 to 0.5 m and seldom up to 1.0 m. Conventional rock support system, consisting of fibre re-enforced shotcrete and rebar rock bolts, has regularly failed under these conditions. As part of Ground Support Research Initiative at Luleå University of Technology a monitoring program was designed to measure ground deformation and the response of the ground support system. Numerical modelling was conducted to capture the responses as observed during monitoring. The numerical models revealed all the typical mechanisms of instability that have been conceptualized through observations and earlier studies. Talc obviously was the most influential lithology that controlled the deformation characteristics of the stope and ultimately on the rock support system. Combinations of bending, bulging, shearing and tensile mechanisms induced a complex loading pattern on the rock support system. Often the rock bolts, for example, would experience all of these mechanisms at once or during different stages of the excavation rounds as a cut is developed.